2002
DOI: 10.1523/jneurosci.22-14-06019.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rac1-Mediated Endocytosis during Ephrin-A2- and Semaphorin 3A-Induced Growth Cone Collapse

Abstract: Negative guidance molecules are important for guiding the growth of axons and ultimately for determining the wiring pattern in the developing nervous system. In tissue culture, growth cones at the tips of growing axons collapse in response to negative guidance molecules, such as ephrin-A2 and semaphorin 3A. The small GTPase Rac1 is involved in growth cone collapse, but the nature of its role is not clear. Rac1 activity assays showed that Rac1 is transiently inactivated after treatment with ephrin-A2. Ephrin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 40 publications
6
137
1
2
Order By: Relevance
“…Although many studies have demonstrated the importance of Rac1 for axon outgrowth and guidance (Kuhn et al, 1998;Jurney et al, 2002;Ng et al, 2002;Shekerabi and Kennedy, 2002), these studies have focused on the role of Rac1 in promoting actin polymerization during leading edge protrusion and endocytosis. Here, we show that Rac1 also supports axon outgrowth by promoting point contact formation, which leads to stabilization of protrusions.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have demonstrated the importance of Rac1 for axon outgrowth and guidance (Kuhn et al, 1998;Jurney et al, 2002;Ng et al, 2002;Shekerabi and Kennedy, 2002), these studies have focused on the role of Rac1 in promoting actin polymerization during leading edge protrusion and endocytosis. Here, we show that Rac1 also supports axon outgrowth by promoting point contact formation, which leads to stabilization of protrusions.…”
Section: Discussionmentioning
confidence: 99%
“…The small GTPase Rac1 is required for growth cone collapse; however, it does not mediate actin depolymerization during collapse. Rather, Rac1 mediates endocytosis during growth cone collapse (Jin and Strittmatter, 1997;Jurney et al, 2002). Together, these data suggest that endocytosis is part of the biological mechanism that mediates the response to repulsive guidance cues.…”
Section: Tuc-4b May Regulate Vesicle Function In the Growth Conementioning
confidence: 93%
“…Stimulation of growth cones by semaphorins or ephrins induces endocytosis in the growth cone (Fournier et al, 2000;Jurney et al, 2002). However, endocytosis is not stimulated by cytochalasin B, suggesting that endocytosis is not a nonspecific consequence of collapse but rather the specific result of intracellular signaling in response to guidance cues.…”
Section: Tuc-4b May Regulate Vesicle Function In the Growth Conementioning
confidence: 99%
“…Recent work has made it clear that Sema3A signaling involves several intracellular pathways mediating a variety of cellular responses (for review, see Pasterkamp and Kolodkin, 2003). After the binding of Sema3A to the coreceptor complex consisting of members of the Plexin-A (PlexA) and neuropilin-1 (NRP1) families of proteins (He and Tessier-Lavigne, 1997;Kolodkin et al, 1997;Takahashi et al, 1999;Tamagnone et al, 1999), neuronal growth cones collapse as a result of the dramatic rearrangement of the actin cytoskeleton and endocytosis of the plasma membrane (Luo et al, 1993;Fournier et al, 2000;Jurney et al, 2002;Castellani et al, 2004). A role for Rho-like GTPases (Jin and Strittmatter, 1997;Zanata et al, 2002;Turner et al, 2004;Toyofuku et al, 2005), protein phosphorylation (Aizawa et al, 2001;Eickholt et al, 2002;Mitsui et al, 2002;Sasaki et al, 2002), RanBPM (Togashi et al, 2006), and members of the collapsin response mediator protein (CRMP) family (Goshima et al, 1995;Deo et al, 2004) have all been shown to play a role in Sema3A signal transduction.…”
Section: Introductionmentioning
confidence: 99%